A study on motivating factors among call center agents at ePLDT Ventus - Bautista, Frizel L.; Ferrer, Febie Grace A.; Ibarra, Manuel R., Jr; Omes, Angeli Pearl B.; Sabandal, Rona A.
The study on human motivation has been one of the most critical milieus in the field of management and psychology. Since the materialization of management as an independent science in the late 19th century, many theorists have come up with their fortes in speculating on the nature of human beings particularly in the workplace. Until now, motivation in the workplace remains one of the most important fields of academic inquiry and learning. A continuous study on this subject matter is crucial to the development of knowledge leading to new findings or theories that may be of help not only to the theorists and academicians themselves but most especially to the organization and its people where application of such theories may be appropriate. The growth of the call center industry in the Philippines has been relentless lately. They have been providing job opportunities among the labor force particularly in Iloilo City. ePLDT Ventus is an organization that employs people who are bound by some dynamics that lead them to work thus Ventus is no exemption to the study of motivation, particularly among the call center agents. Among others there is also need to identify the stresses they encounter in ePLDT Ventus which may affect of working in a call center may also gauge the workers' motivation to work.